REPRESENTASI NILAI-NILAI EDUKASI DALAM IKLAN LAYANAN MASYARAKAT BERDASARKAN ANALISIS SEMIOTIKA ROLAND BARTHES(Direktorat Promosi Kesehatan dan Pemberdayaan Masyarakat Kementrian Kesehatan Republik Indonesia Versi Cegah Covid-19 dengan Protokol 5M & Vaksinasi) - Bagaskoro Bisono Putro (2023)
This research is a semiotic study on Public Service Advertisements entitled "Prevent Covid-19 with 5M & Vaccination". This study aims to determine the meaning of the elements of educational value in each scene in the advertisement. As well as analyzing the meaning of denotation, namely the meaning that is seen directly, connotation, namely the meaning that actually occurs and is subjective, and myth, namely the meaning that is formed in a community group and is closely related to educational value factors. This Public Service Announcement will be analyzed using Roland Barthes' semiotic analysis. This study uses a descriptive qualitative methodology with Roland Barthes's semiotic analysis based on communication concepts and educational values from experts that researchers obtain from books, journals, and other scientific literature to explain the meaning in the form of denotations, connotations, and myths of each message. delivered. The results of the study show that the symbols of educational value elements in the Public Service Advertisement "Prevent Covid-19 With 5M & Vaccination" are represented through various kinds of gestures and objects. The researcher's suggestion for further research is to conduct research on the representation of other values in Public Service Advertisements with variations on concepts, reading materials, and theories as references when carrying out stronger significance.